A case of blurred vision and viral keratitis postcataract surgery. (December 2018) - Ding, Tong; Chou, Yilin; Jiang, Xiaodan; Qiu, Weiqiang; Shi, Danna; Wu, Feng; Li, Xuemin
An 84-year-old woman underwent cataract surgery. In 3 weeks, the right eye presented with blurred vision, corneal irritation and photophobia. After 5 weeks, symptoms in the right eye worsened and ganciclovir was prescribed. Based on clinical findings, viral keratitis was suspected; real-time PCR (RT-PCR) assay of tear samples from the right eye was performed. Thereafter 1 week, the left eye also exhibited similar symptoms. The RT-PCR was performed using a sample from the left eye; the results suggested the presence of Epstein–Barr virus and cytomegalovirus. A combination of confocal microscopy and RT-PCR assay of tear samples can supplement slit-lamp observation and help diagnose atypical and refractory postcataract surgery viral keratitis.